Revision of the genus Luridiblatta (Blaberoidea, Ectobiidae, Ectobiinae) - Bohn, Horst (Zootaxa, 2022)
The present paper deals with the revision of Luridiblatta a genus having an almost circum-mediterranean distribution. The genus contains 10 species of which 7 are new; they can be aligned to 3 species-groups: the longitubulata-group with the species L. longitubulata sp. nov., L. gibberosa sp. nov., L. fenestrata sp. nov., and L. vesiculosa sp. nov.; the trivittata-group with L. trivittata and L. habbachii sp. nov.; and the beybienkoi-group with L. quadrivittata, L. cyprica sp. nov., L. beybienkoi and L. graeca sp. nov. The species descriptions are accompanied by numerous photographs, a taxonomic key to males, and a cladogram showing the presumed interspecific relationships. Study of the morphology elucidates an unusually high variation in shape and structure of the abdominal tergites T6, T7 and T8. In the species with strongly derived T6 the latter is characterised by enigmatic structures giving the impression for serving as a kind of a drainage system.